Procesos aculturativos en las manifestaciones folklóricas de la comunidad quechua wayku - Hidalgo Pozzi, Rossana Herminia (2013)
The research "ACULTURATIVE processes in the Center village community QUECHUA WAYKU" work has been developed as an alternative to preserve culture and improve the standard of living of the inhabit. The research aims to expose different processes acculturative that has been happening in the village community Quechua Wayku Centre of the town of Lamas, with the aim of recovering and conserving lamas Quechua culture. The Acculturative processes in the community Wayku Quechua of the Lamas district is predominantly presented through forms of assimilation and induction; and significantly influencing current folklore manifestations. The assimilation as a form of the acculturative process occurs primarily through the modality of syncretism, induction, also as a form of the aculturativo process, are primarily through patterns of symbiosis and deculturation; significantly influencing the current folk demonstrations of community quechua Wayku in the District of Lamas. Taking into account the contrasting hypothesis technique, the present is a descriptive research. The implementation of surveys at depth was directed to heads of households according to the reality of the community and as a live entity family economic movement. The methods were used: Deductivo, to apply the concepts and theories to the specific case of the Center village minor Quechua Wayku. Inductive, with the aim of obtaining generalizations based on observations, interviews and selected specific processes. This process-based acculturative and other research has determined that the Center village community Quechua Wayku is giving a process marked aculturativo. 21% Of the population speak Spanish, 80% of the folk demonstrations were already lost in its entirety. And 20% still maintain these customs traditions that in an era of history the community was its folkloric representation. The population of the CPCQW, this lost the habit of communicating with the quechua language, by the permanent contact with the other society, not preserved the native typical dress, combined of both companies to dress, the religious rituals are not already preserved.